Mobsters, Unions and Feds: The Mafia and the American Labor Movement - Gould, Anthony M. (Relations industrielles / Industrial Relations, 2007)
The article reviews the book, "Mobsters, Unions and Feds: The Mafia and the American Labor Movement," by James B. Jacobs.
Keywords: American history; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Organized crime; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z